Contemporary trends in global foreign direct investment flows - Stojadinović-Jovanović Sandra (Međunarodni Problemi)
It is not necessary to explain the importance of foreign direct investment, particularly in less developed countries, bearing in mind the numerous theoretical and empirical papers that confirm their importance and effects that the inflow of these investments in the country can make. The movement of these investments on the global level is characterized by significant changes, especially in recent years, in their volume, geographically distribution as well as in the conditions in which they take place - conditions of instability and crisis interruptions, growing regional and interregional integration and altered foreign direct investment policies. Trends in their movements are mirrored in individual countries, stressing on the need for their continuous monitoring and detailed analysis. Therefore the paper will identified the key trends that characterize the contemporary global flows of foreign direct investments.